Postoperative Sagittal Balance Has Only a Limited Role in the Development of Adjacent Segment Disease After Lumbar Spine Fusion for Degenerative Lumbar Spine Disorders: A Subanalysis of the 10-year Follow-up Study. Issue 19 (1st October 2022) - Toivonen, Leevi A.; Mäntymäki, Heikki; Häkkinen, Arja; Kautiainen, Hannu; Neva, Marko H.
Abstract : Study Design: Retrospective additional analysis of a prospective follow-up study. Objectives: We aimed to find out whether poor postoperative sagittal alignment increases revisions for adjacent segment disease (ASD) after lumbar spine fusion (LSF) performed for degenerative lumbar spine disease. Summary of Background Data: Revisions for ASD accumulate over time after LSF for degenerative lumbar spine disease. The etiology of ASD is considered multifactorial. Yet, the role of postoperative sagittal balance in this process remains controversial. Materials and Methods: A total of 215 consecutive patients who had undergone an elective LSF surgery for spinal stenosis with (80%) or without (20%) spondylolisthesis were analyzed. Spinal reoperations were collected from the hospital records. Preoperative and postoperative sagittal alignment were evaluated from standing radiographs. The risk of revisions for ASD was evaluated by Cox proportional hazards regression models. Results: We did not find the poor postoperative balance [pelvic incidence−lumbar lordosis (LL) >9°] to significantly increase the risk of revisions for ASD: crude hazard ratio (HR)=1.5 [95% confidence interval (CI): 0.8–2.7], adjusted (by age, sex, pelvic incidence, fusion length, and the level of the caudal end of fusion): HR=1.7 (95% CI: 0.9–3.3). We found higher LL outside the fusion segment (LL−segmental lordosis) to decrease the risk of revisions for ASD: HR=0.9 (95% CI: 0.9–1.0). Conclusion: Poor sagittal balance has only a limited role as a risk factor for the revisions for ASD among patients with degenerative spinal disease. However, the risk for ASD might be the greatest among patients with reduced spinal mobility.